CoP/Fe‐Co9S8 for Highly Efficient Overall Water Splitting with Surface Reconstruction and Self‐Termination. Issue 34 (21st October 2022) - Chen, Xinhong; Cheng, Yumeng; Wen, Yunzhou; Wang, Yaya; Yan, Xiao; Wei, Jun; He, Sisi; Zhou, Jia
Abstract: Highly efficient electrochemical water splitting is of prime importance in hydrogen energy but is suffered from the slow kinetics at the anodic oxygen evolution reaction. Herein, combining the surface activation with the heterostructure construction strategy, the CoP/Fe‐Co9 S8 heterostructures as the pre‐catalyst for highly efficient oxygen evolution are successfully synthesized. The catalyst only needs 156 mV to reach 10 mA cm −2 and keeps stable for more than 150 h. Inductively coupled plasma optical emission spectrometry, in situ Raman spectroscopy and density functional theory calculations verify that the introduction of Fe can promote the formation of highly active Co(IV)–O sites and lead to a self‐termination of surface reconstruction, which eventually creates a highly active and stable oxygen evolution catalytic surface. Besides, the catalyst also demonstrates high hydrogen evolution reaction activity with an overpotential of 62 mV@10 mA cm −2 . Benefiting from its bifunctionality and self‐supporting property, the membrane electrode assembly electrolyzer equipped with these catalysts achieves high overall water splitting efficiency of 1.68 V@1 A cm −2 . Abstract : By combining surface activation with a heterostructure construction strategy, a CoP/Fe‐Co9 S8 heterostructure is successfully constructed as a high‐efficiency electrocatalyst. Benefiting from the zero‐gap architecture and the highly efficient performance, the membrane electrode assembly (MEA) electrolyzer only needs 1.68 V to reach 1 A cm −2, achieving low‐cost and high‐efficiency overall water splitting.